26Al-26Mg isotopic studies in some calcium-aluminium-rich inclusions and chondrules from unequilibrated chondrites - Mishra, Ritesh Kumar; Marhas, Kuljeet Kaur; Trieloff, Mario (Current science, 2023)
Calcium-aluminium-rich inclusions (CAIs) and chondrules are the oldest dated components of chondrites. They record the events and processes during the formation and early evolution of the solar system in their morphology, mineral phases and isotopic compositions. Al-26-Mg-26 isotopic systematics of two CAIs from Leoville (CV3.1-3.4), two chondrules from Queen Alexandra range 99177 (CR3.00), one mega chondrule from Semarkona (LL3.00), and a plagioclase rich chondrule from Chainpur (LL3.4) were carried out to understand the formation processes of these rare kinds of objects and to obtain constraints on early solar system events and processes. Petrographic and isotopic properties of Leoville CAI 1 (Type B2) suggest its formation c. 0.1 Ma after typical non-igneous CAIs characterized by the canonical ratio of Al-26/Al-27 = 5.25 x 10(- 5), from a partial melt heated to a maximum temperature of similar to 1420 degrees C and cooled slowly at <= 0.5 degrees C/h. Leoville CAI 3 (Type A) plausibly formed early within 1 Ma of the canonical CAI value and subsequently experienced parent body aqueous alteration. The analysed chondrules did not yield significant Mg-26 excess due to their small Al/Mg ratio or resetting by secondary processes.